PREVALENCE OF WEAK D PHENOTYPE IN BLOOD DONORS: A STUDY FROM TERTIARY CARE HOSPITAL - Hameed, Mehreen; Raziq, Fazle (Journal of Postgraduate Medical Institute, 2021)
Objective: To determine the prevalence of weak D phenotype among blood donor population. Methodology: This cross-sectional review was conducted at Rehman Medical Institute, Peshawar from October 2018 to September 2019 and involved 4361 voluntary blood donors. Blood samples obtained for ABO and Rh D blood grouping were tested through conventional test tube technique. Agglutinating commercially available monoclonal anti-D sera were used for Rh D status detection. Du-testing was performed to identify weak-D phenotype. MS Excel and SPSS version-22 were used hands for statistical analysis. Results: A total of 4361 blood samples were taken from recruited healthy blood donors (one sample per donor). Out of these 3786 (86.8%) were Rh D positive while 575 (13.2%) were Rh D negative. Among Rh D negative cases, three (0.5%) were weak-D positive constituting 0.5% among Rh D negatives and 0.06% from total donors screened. Conclusion: This study concluded a very small prevalence of weak D in blood donor population. It is recommended that weak-D phenotype detection in Rh negative donors must be considered as an essential part of blood transfusion investigations to prevent risk of alloimmunization in recipients.